Knowledge management and profitability of the casual dining restaurant in Malaysia - Othman, Abdul Rahim (2008)
This study examines the relationship between knowledge management and profitability. A theoretical model that is based on the resource-based view of the firm is developed and tested empirically. The model includes three main components of knowledge management which are knowledge actualization, knowledge dissemination and responsiveness to knowledge where the performance of the firm is measured based on profitability. Survey data of 164 casual dining restaurant’s managers in the Klang Valley, Malaysia was used to test the relationship between the main constructs in the study. Analysis reveals that only responsiveness to knowledge has a positive relationship with profitability. These findings suggest that profitability of the casual dining restaurant in Malaysia depends on how well the restaurant responds to knowledge of its customers, competitors and market conditions.